2006
DOI: 10.1002/hpm.855
|View full text |Cite
|
Sign up to set email alerts
|

A review of the experience of hospital autonomy in Pakistan

Abstract: SUMMARYThis paper examines the recent trends in public hospital autonomy as an integral part of health systems reforms. It reviews literature produced on the subject across a range of developing countries and explores varying viewpoints, arguments, and rationale for hospital autonomy developed over the past two decades. It then leads onto a discussion of two experiences of autonomy reforms in Pakistan: the provinces of Punjab and NWFP. Derived from the lessons learned from these initiatives, a set of guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
2
26
0
1
Order By: Relevance
“…It was suggested that transforming the public hospitals to autonomous units can improve its management, reduce allocation of its public resources, and increase the accountability of these hospitals . This transformation is only possible by reducing direct government control and assigning the daily decisions to the hospitals' executive managers instead of top‐level managers …”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that transforming the public hospitals to autonomous units can improve its management, reduce allocation of its public resources, and increase the accountability of these hospitals . This transformation is only possible by reducing direct government control and assigning the daily decisions to the hospitals' executive managers instead of top‐level managers …”
Section: Introductionmentioning
confidence: 99%
“…But McPake () could find no evidence for increased productivity or improvements in quality in Columbia. Pearson () also states that accountability has been improved in terms of timely and accurate financial reports to government, but that there has been no change in accountability to local communities (Abdullah and Shaw's findings concerning Pakistan may be an exception). Local managers have found that they have more freedom in terms of day to day management, at least.…”
Section: Public Hospital Reform Across the Worldmentioning
confidence: 97%
“…But most have made little change in respect of personnel management. In general, staff has remained on civil service terms and conditions (for example, in the Northwest Frontier Province in Pakistan—Abdullah and Shaw, ). As noted in respect of Europe (Saltman et al ., ), politicians and senior civil servants are reluctant to give hospitals a significant degree of autonomy, because of the sensitive and politicized nature of healthcare.…”
Section: Public Hospital Reform Across the Worldmentioning
confidence: 99%
“…According to Kumaranayake (1997), while increasing privatization of healthcare delivery has become central to health sector reforms in many countries, the problems of private institutions, financing, and delivery of health services are dealt mainly through regulation. Since privatization is partly in response to poor or unprofessional patient care and mismanagement of resources in the public sector, the need for regulation is even greater (Abdullah and Shaw, 2007).…”
Section: Regulationmentioning
confidence: 99%